Professor Ângelo Machado: career, scientific contributions, and the iconic neuroanatomy book - Alex Tiburtino MEIRA; Gustavo Leite FRANKLIN; Francisco CARDOSO; Hélio Afonso Ghizoni TEIVE; Orlando Graziani Povoas BARSOTTINI; José Luiz PEDROSO (Arquivos de Neuro-Psiquiatria)
ABSTRACT Professor Ângelo Barbosa Monteiro Machado (May 22, 1934 to April 6, 2020) was one of the most outstanding and respected professors in the Brazilian history. He worked broadly as a professor, neuroscientist, writer, dramaturgist, neurobiologist, and entomologist. The publication of the neuroanatomy book is pioneer, revolutionary, and iconic in the history of academic medical education in Brazil. In the literature field, he also wrote many books in which he adapted scientific knowledge to children. In this article, the authors approach the academic life of Professor Ângelo Machado and the steps that culminated in the most renowned Brazilian textbook of neuroanatomy: Neuroanatomia Funcional.